Effect of journal misalignment on the static characteristics of an innovative journal bearing with adjustable elements in load-on-pad and load-between-pad configurations. Issue 4 (28th August 2020) - Girish, H.; Pai, Raghuvir
Abstract : Purpose: The purpose of this paper is to theoretically analyze an innovative form of variable bearing configuration having four pads with unique adjustability principle operated under journal misaligned conditions. The parameters such as load positions, degrees of misalignment (DM) and pad adjustment configurations influencing the steady-state performance of the four-pad adjustable bearing are detailed in this paper. Design/methodology/approach: The proposed adjustable pad geometry possesses the ability to undergo radial and tilt motions in both inward and outward directions. Analysis is carried out by considering journal misalignment in vertical and horizontal planes with bearing modelled for load-on-pad and load-between-pad configurations. The film thickness equation derived to incorporate the radial and tilt adjustment parameters is further modified to accommodate the different load orientations and misaligned journal conditions. The pressure field equation is solved by applying finite-difference technique combined with Gauss Siedel iterative method. Findings: At higher DM, peak pressures generated in the minimum film thickness region near the pad ends highly influences the bearing load carrying capacity. Results indicated that the adjustable four-pad bearing geometry is highly efficient in withstanding the journal misalignment by radially displacing and tilting the four pads in negative directions. Originality/value: For bearing designers, this research highlights the importance of considering the misalignment factor during the design stages of an adjustable journal bearing. The proposed adjustability concept is proven to be effective enough to improve the bearing performance and, in turn, withstand the journal misalignment.